Sistem Monitoring Perjalanan Dinas Berbasis Web (Studi : Badan Perencanaan Pembangunan Pemerintah Daerah Kabupaten Ngawi) - Cahyo Yudha Putranto; Riyan Abdul Aziz; Febrianta Surya Nugraha (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
In the progress of information technology and knowledge, data processing by computer played a significant role in the field of information. But many institutions government still has not implemented the optimal monitoring systems, particularly in the management of the official travel. This research focuses on the monitoring system official travel web based development planning board the kabupaten government ngawi. This difficulty while manual is the use of ms.Office word and excel in the management of official travel, led to the mistake and the.To deal with this problem, the researchers devised a system of the web based covering management accountability, that in the official travel. This study by using the method proposed method of development rad.The design participation of users who plays the role of crucial revision in software design the specifications.The result showed that these information systems capable of accelerating and loosening the process of making a official travel.The implementation of this system, expected the finance division directorate of trading businesses able to manage official travel more efficiently in accordance with the regulation.This study produced recommendations for similar institution to adopt similar solutions in the management of official travel.